Research on wireless spectrum allocation and utility evaluation of cross-domain multi-slot radio. (October 2022) - Li, Xueqing; Liu, Weifeng; Zhu, Junwu
Abstract: The existing spectrum use authorization adopts the large-period and large-area allocation mode, and users exclusively use the right to use the spectrum, resulting in the idle spectrum of multiple time slots and regions and a low utilization rate. This paper proposes a cross-domain, multi-slot Wireless Spectrum Allocation Mechanism (CMWSA) from a fine-grained spatiotemporal perspective. The bilateral spectrum auction model includes the buyer's location, the start and end time, and the interference radius in the auction information, and the multi-spectrum buyer virtual grouping algorithm is designed. By classifying the spectrum and constructing the interference matrix, a cross-domain, multi-slot, spatiotemporal reuse Wireless Spectrum auction mechanism is proposed to improve the utilization of the idle spectrum and increase users' satisfaction. Simulation results show that CMWSA can improve the spectrum utilization rate of secondary users, meet the diverse needs of secondary users, and improve the spectrum reuse rate. Graphical abstract: Highlights: This model can satisfy the seller to hold multiple heterogeneous spectrum segments. Virtual nodes are used to realize multi-segment spectrum auction. The seller multi - spectrum auction is realized by spectrum classification The conflict matrix is constructed to realize the time and space reuse of spectrum. The proposed winner decision algorithm can effectively improve the unfairness.